2018
DOI: 10.29312/remexca.v9i2.1089
|View full text |Cite
|
Sign up to set email alerts
|

Jaguar: cultivar de chile habanero para México

Abstract: La siembra de chile habanero (Capsicum chinense Jacq.) en México se encuentra concentrada en alrededor de 80% en la península de Yucatán. Aproximadamente 50% del área dedicada a esta hortaliza se siembra con materiales criollos, el resto con variedades de polinización libre y un área mínima con híbridos de reciente formación, desarrollados por empresas transnacionales, lo que propicia fuga de divisas que afecta la economía del país. Por lo antes mencionado, el objetivo de este trabajo fue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 0 publications
1
1
1
5
Order By: Relevance
“…The results described are similar to those reported by Tucuch et al [32] and Peña [33], who found average values of 25.4 mm for the equatorial diameter of the fruit in habanero pepper genotypes. However, Ramírez Meraz et al [19] pointed out that the Jaguar variety produces fruits with a length ranging from 3.8 to 5.5 cm, and diameters between 2.5 and 3 cm, while the average weight of the fruit was 6.5-10 g, values that are higher than those obtained in this work.…”
Section: Agronomic Parameterscontrasting
confidence: 82%
“…The results described are similar to those reported by Tucuch et al [32] and Peña [33], who found average values of 25.4 mm for the equatorial diameter of the fruit in habanero pepper genotypes. However, Ramírez Meraz et al [19] pointed out that the Jaguar variety produces fruits with a length ranging from 3.8 to 5.5 cm, and diameters between 2.5 and 3 cm, while the average weight of the fruit was 6.5-10 g, values that are higher than those obtained in this work.…”
Section: Agronomic Parameterscontrasting
confidence: 82%
“…This is the case of the C. chinense J. variety Jaguar with a harvest period of three to seven months in open field, and more than two years in protected conditions. In the Peninsula of Yucatan, 93% of habanero peppers are cultivated under an open field [ 13 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…10,13 La especie C. chinense es de pulpa firme, presenta forma de trompo con áreas hundidas. Sus frutos son de color verde esmeralda en estado inmaduro hasta alcanzar color anaranjado brillante en estado de madurez (figura 1C), miden de 3 cm a 5 cm de longitud y pesan de 6 g a 10 g 10,14 , el número de semillas en una especie de C. chinense conocida como "ají mochero" es de 16 semillas por fruto. 15 Los frutos de la especie C. frutescens tienen una longitud y peso de 2.2 cm a 4.1 cm y de 1 g a 2.30 g, respectivamente, son alargados, de ápice puntiagudo (figura 1D), esta especie contiene entre 15 y 16 semillas de color amarillo por fruto.…”
Section: Morfología Y Composición De Las Especies Domesticadas Del Género Capsicumunclassified